Advanced planarization techniques for deep sub-micron applications - Lim, Victor Seng Keong. (2008)
In this work, the evolution of step height, film thickness and unformity, on both the STI test structures and SDRAM structure throughout the CMP process were characterized in detailed. Comparision made among the newly proposed scheme and the conventional processes such as Direct Polish (DP) Scheme and the Reverse Mask (RT) Scheme were also presented.